Penerapan Quality Function Deployment untuk Meningkatkan Kualitas Pelayanan Berdasarkan Kebutuhan Pelanggan Restoran Cepat Saji Omah Gedhi Steak dan Penyet di Kota Kendal - Fitri, Miladia Dliyaul; Cahya, Handy Nur (Faculty of Economics and Business Universitas Dian Nuswantoro, 2023)
The population in this study were consumers of Omah Gedhi Steak and Penyet Fast Food Restaurants in Kendal City. The samples taken in this study used a purposive sampling technique, with as many as 100 respondents. The data analysis method used comes from primary data sources and additional (secondary) data as part of the Quality Function Deployment (QFD) process. The tests carried out are the Validity Test and Reliability Test using SPSS 24 assistance. Based on the data analysis carried out, conclusions were obtained using the Quality Function Deployment (QFD) method which uses a matrix from the House of Quality (HoQ) which can be used in answering the research questions. The Left Room of the House of Quality shows what are the priority needs of consumers namely the dimensions of